A biphasic response of polymerized Type 1 collagen architectures to dermatan sulfate. Issue 9 (9th March 2021) - Jyothsna, Konkada Manattayil; Sarkar, Purba; Jha, Keshav Kumar; A. S., Lal Krishna; Raghunathan, Varun; Bhat, Ramray
Abstract: Collagen I, the most abundant extracellular matrix (ECM) protein in vertebrate tissues provides mechanical durability to tissue microenvironments and regulates cell function. Its fibrillogenesis in biological milieu is predominantly regulated by dermatan sulfate proteoglycans, proteins conjugated with iduronic acid‐containing dermatan sulfate (DS) glycosaminoglycans (GAG). Although DS is known to regulate tissue function through its modulation of Coll I architecture, a precise understanding of the latter remains elusive. We investigated this problem by visualizing the fibrillar pattern of fixed Coll I gels polymerized in the presence of varying concentrations of DS using second harmonic generation microscopy. Measuring mean second harmonic generation signal (which estimates the ordering of the fibrils), and surface occupancy (which estimates the space occupied by fibrils) supported by confocal reflectance microscopy, our observations indicated that the effect on fibril pattern of DS is contextual upon the latter's concentrations: Lower levels of DS resulted in sparse disorganized fibrils; higher levels restore organization, with fibrils occupying greater space. An appropriate change in elasticity as a result of DS levels was also observed through atomic force microscopy. Examination of dye‐based GAG staining and scanning electron microscopy suggested distinct constitutions of Coll I gels when polymerized with higher and lower levels of DS. We observed that adhesion of the invasive ovarian cancer cells SKOV3 decreased for lower DS levels but was partially restored at higher DS levels. Our study shows how the Coll I gel pattern‐tuning of DS is of relevance for understanding its biomaterial applications and possibly, pathophysiological functions.